Negative Emotional State dan Cyberbullying Pada Mahasiswa - Muzdalifah, Fellianti; Deasyanti, Deasyanti (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
Cyberbullying is a form of aggressive behavior by using telecommunications media with the aim of embarrassing, threatening, and intimidating certain parties. Cyberbullyings widely applied using mobile media, online chatting (whatsapp, LINE), e-mail, and also online social media such as Facebook, Instagram,or to personal blogs. Cyberbullying evoked negative emotional states namely depression, anxiety, and stress in cyberbullies and cybervictimization. This study provided evidence indicating that college students who experienced in cyberbullying at least 1 week, either cyberbullies or cybervictimization had differences level of negative emotional states,namely depression, anxiety, and stress. The data collection was used the DASS-42 scale to measure negative emotional states (depression, anxiety, and stress). The level of depression, anxiety, and stress were consisted of normal, mild, moderate, severe, and very severe. Meanwhile, Revised Cyber ​​Bullying Inventory-II (RCBI-II) was used to collect cyberbullying data and determined the role in cyberbullying (cyberbullies and cybervictimization). The respondents was 48 cyberbullies and 38 cybervictimization. The result showed that most of 51,1% total of cyberbullies and cybervictimization did not have depression and the rest had different levels of depression. Related to anxiety, cyberbullies showed that 52.1% cyberbullies did not have anxiety. Otherwise in cybervictimization, 28.9% did not have anxiety and another 28.9% were at anxiety levels.Then related to stress, most of 52,3% total of cyberbullies and cybervictimization did not have stress and the rest had different levels of stress. Keywords: cyberbullying, negative emotional state, college students.